A comparison of 3, 4, 6a, 7, 10, 10a‐hexahydro‐7, 10‐epoxypyrimido[2, 1‐a]isoindol‐6(2H)‐one and 2‐(2‐aminoethyl)‐3a, 4, 7, 7a‐tetrahydro‐1H‐4, 7‐epoxyisoindole‐1, 3(2H)‐dione: structural and reactivity differences of two homologous tricyclic imides. (9th May 2013) - Mitchell, Lauren A.; Stanley, Julie M.; Espinosa De Hoyos, Liliana; Holliday, Bradley J.
<x xml:space="preserve">Abstract</x> The crystal structures of 3, 4, 6a, 7, 10, 10a‐hexahydro‐7, 10‐epoxypyrimido[2, 1‐a]isoindol‐6(2H)‐one, C11H12N2O2, and 2‐(2‐aminoethyl)‐3a, 4, 7, 7a‐tetrahydro‐1H‐4, 7‐epoxyisoindole‐1, 3(2H)‐dione, C10H12N2O3, two tricyclic imides, show one and two molecules in the asymmetric unit, respectively. Intermolecular hydrogen‐bonding interactions are observed in both compounds.